PENGARUH INSENTIF PAJAK DAN INSENTIF NON PAJAK TERHADAP MANAJEMEN LABA SAAT TERJADI PENURUNAN TARIF PAJAK PENGHASILAN BADAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Marselina Hamijaya (Universitas Katolik Soegijapranata Semarang, 2015)
The decline in corporate income tax rates in Indonesia as stipulated in Law No.36 Year 2008 delivers advantages for companies that obtain lightening the tax burden which must be paid by the company. However, on the other hand a decrease in income tax rates The agency raises opportunist attitude managers to manage earnings in order Companies can save on the tax burden to be paid. The manager will organize the number of reported earnings so that the burden of tax paid is not burdensome company. Earnings management action was influenced by tax incentives and incentives non tax. The purpose of this study was to verify whether the tax incentive and non-incentivetax effect on earnings management and whether the reduction in income tax ratesbody effect on earnings management. The sample in this research companylisted on the Indonesia Stock Exchange in 2008 until 2010. Data analyzation used in this study is multiple regression and independent t-test. The independent variables in this study is a tax incentive that consists of planningtaxes, deferred tax expense and deferred tax assets; non-tax incentives consisting ofearnings pressure, debt level, earnings bath, and the size of the company. dependent variablesin this research is earnings management. The results of this study indicate that earnings management occurs when the tariff reductionCorporate income tax is significantly affected by deferred tax expense, earningspressure, level of debt, the size of the company, and earnings bath and a decrease in tax ratesCorporate income proved to have a significant effect on earnings management. Whiletax planning and deferred tax assets did not significantly influenceprofit management.